Sistem Monitoring dan Kontrol Penyiraman Tanaman Otomatis Menggunakan Sensor Soil Moisture dan IoT - Rindy Ayu Wantiny; Nur Ahmad Fadil; Rhoma Taufik Akbar Harahap; Muhammad Aldi (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
This study aims to design and test an automatic plant watering monitoring and control system based on the Internet of Things (IoT) to address problems associated with manual watering, which is often inconsistent, inefficient, and may lead to under watering or over watering. The system was developed using a capacitive soil moisture sensor, NodeMCU ESP8266 microcontroller, relay module, water pump, and the Blynk application as a remote monitoring and control interface. The sensor detects soil moisture levels in real time and sends data to the microcontroller, which processes the readings and controls the pump automatically based on predetermined moisture thresholds. The test results show that the system can monitor soil moisture accurately, activate the pump when the soil condition is dry, and stop watering when the soil reaches the optimal moisture level. The system is also able to maintain soil moisture within the required range and reduce water use compared to conventional manual watering. Therefore, the proposed IoT-based watering system provides an effective, practical, and efficient solution to support automatic plant care and improve watering accuracy in household cultivation practices.